THE INFLUENCE OF EXPOSURE TO THE EDUCATIONAL CONTENT OF THE TIKTOK ACCOUNT @vmuliana ON THE INFORMATION NEEDS FOR CAREER PREPARATION OF GENERATION Z FOLLOWERS (CASE STUDY OF IBNU CHALDUN UNIVERSITY STUDENTS, JAKARTA) - Anwar Sjani; Rini Haryani; Riska Ramdani (Jurnal Ilmiah METADATA, 2026)
The unemployment rate among generation Z in Indonesia is relatively high, especially in the 15-24 year old age group (16.42%) and 25 -29 year olds (3.08%), indicating significant challenges in entering the job market even though this generation is known to be adaptive to technology. Based on data from the Engineering Career Center (ECC), lack of career preparation education is one of the main causes, such as lack of self-confidence during interviews, difficulty recognizing one's potential, and lack of information about the world of work. On the other hand, TikTok is used by creators such as @vmuliana (Vina Muliana) to deliver career education content. This research aims to analyze the influence of exposure to the educational content of the TikTok @vmuliana account on fulfilling Generation Z's career preparation information needs among students at Ibnu Chaldun University, Jakarta. This quantitative research uses a non-probability sampling technique, purposive sampling, with 50 respondents who meet certain criteria. The t test results showed a positive and significant effect (p = 0.000 < 0.05), with a coefficient of determination of 61.1%. The findings support the S-O-R theory and media exposure theory, and confirm the potential of social media as an effective career education tool for the younger generation.